Study of the effect of the compaction level on the hydrodynamic properties of loamy sand soil in an agricultural context - Mbarki, Yasmin; Gumiere, Silvio José; Celicourt, Paul; Brédy, Jhemson (Frontiers in Water, 2023)
Agricultural soil compaction adversely affects crop performance and should be avoided through appropriate soil management strategies. Previous research shows a lack of comprehensive studies on the impact of different levels of soil compaction on hydrodynamic properties. This study focused on the effect of compaction on soil hydrodynamic properties under unsaturated and saturated conditions using the Hydraulic Property Analyzer (HYPROP) system. We studied the impact of five compaction levels on loamy sand soil samples taken from a potato field in the northern agricultural regions of Quebec, Canada, using four replicates per level. First, the saturated hydraulic conductivity of each sample was measured using the constant-load method. Soil water retention curve (SWRC) and unsaturated hydraulic conductivity data were obtained using the HYPROP evaporation measurement device and a WP4C dew point potentiometer. Sixteen hydraulic soil models in the HYPROP-Fit software were simulated. Our results support the application of the Peters-Durner-Iden (PDI) variant of van Genuchten's bimodal unconstrained model (VGm-b-PDI) for full SWRC estimation based on the root mean square error (RMSE) metric. The VGm-b-PDI model was implemented in HYDRUS-1D software to calculate the amount of irrigation for different compaction levels and provide more accurate estimates of soil hydraulic properties. We simulated soil compaction and irrigation scenarios with the dual-porosity model and the results indicated that soil compaction can strongly influence soil hydraulic properties in different ways. Saturated and unsaturated conductivity decreases with increasing soil compaction. At a moderate level of compaction, the amount of irrigation for potato cultivation was optimal. Overall, the combined methodology of HYPROP and HYDRUS 1D gave excellent results in terms of the hydraulic behavior of compacted soils.